Hardy inequality and the construction of the generator of a C0-group with eigenvectors not forming a basis - Sklyar, G. M.; Marchenko, V. A. (Reports of the National Academy of Sciences of Ukraine, 2015)
The construction of the generator of linearly growing C0-group with simple purely imaginary eigenvalues, which cluster at infinity, and eigenvectors not forming a basis, is presented.